Structural Integrity of Attention Networks in Cross-Modal Selective Attention Performance in Healthy Aging - (:unkn) unknown (My University, 2017)
The influence of structural brain changes in healthy aging on cross-modal selective attention performance was investigated with structural MRI (T1- and diffusion-weighted scans). Eighteen younger (M=26.1, SD=5.7) and 18 older (M=62.4, SD=4.9) healthy adults with normal hearing performed a reaction time (RT) cross-modal selective attention A/B/X task. Participants discriminated syllables presented in either visual or auditory modalities, with either randomized or fixed distraction presented simultaneously in the opposite modality. Within the older group only, RT was significantly slower during random (M=573.24, SE=33.66) compared to fixed (M=554.04, SE=33.53) distraction, F(1,34)=5.41, p=.026. Average gray matter thickness and white matter integrity were lower for older adults, all p.05. However, post-hoc adaptive lasso regressions demonstrated that FA of bilateral SLF predicted RT distraction index, Wald 2=3.88, p=.016. The present results indicate that structural integrity underlying both DAN and VAN may aid in cross-modal selective attention performance, suggesting that communication between the networks, likely via top-down modulation of bottom-up processes, may be crucial for optimal attention regulation.
Keywords: Attention Control; Healthy Aging; White Matter Integrity